Comparison of Physical–Chemical Characteristic and Antibacterial Effect Between Manuka Honey and Local Honey - Sundoro, Ali; K., Nadia; A., Nur; Sudjatmiko, Gentur; Tedjo, A. (Jurnal Plastik Rekonstruksi, 2012)
Background:Honey has positive effects on wound healing due to its properties to decrease inflammatory reaction, assist wound debridement, lessen wound odor, help moisturize the wound, promote wound healing and has antibacterial effect. In this research we try to confirm the benefit of using Indonesian local honey by comparing its efficacy with Manuka honey, which is already known yet still costly and not readily available in Indonesia.Methods: Two kinds of honey above were compared for its physical and chemical properties of antibacterial effects and safety, its acidity (pH) using pH meter, osmotic pressure with indirect measurement using hygroscope and hydrogen peroxide concentration using hydrogen peroxide strip test, also for its bacterial contents using standardized microbiological culture.Results: The measurements of the water activity, pH level,production of hydrogen peroxide, also the bacterial content, showed that there is no significant difference between the manuka honey and the local ones.Discussion: Both of the honey pH levels are still within the normal range of honey pH level (3.5-4.5) which still have the antibacterial properties to inhibit bacterial growth. Both of the honey water activity level are still within the normal range of honey water activity level (0.500–0.650) which still have the antibacterial properties to inhibit bacterial growth. Manuka honey has been known as non peroxide honey that didn’t produce any hydrogen peroxide.Conclusion:Indonesian local honey which has been used in this research has a similar physical–chemical characteristic as Manuka honey; making it a very good alternative source of medicinal honey because of its affordability and availability.